Characterization of Two Mitogenomes of IHyla sanchiangensis/I , with Phylogenetic Relationships and Selection Pressure Analyses of Hylidae - Hong, Yue-Huan; Huang, Hai-Ming; Wu, Lian; Storey, Kenneth B; Zhang, Jia-Yong; Zhang, Yong-Pu; Yu, Dan-Na (Animals (Basel), 2023)
Hylidae is a rich family of Anura that is widely distributed across the world. Previous studies have shown that the Hyla and Dryophytos genera in the Hylidae used to belong to the same genus. The Eurasian species (including Hyla sanchiangensis) originated in North America and spread through the Beringian Land Bridge to Asia during the last ice age. Adaptation to low temperatures may require more energy expenditure. Mitochondria are the center of energy metabolism and, through oxidative phosphorylation, provide most of the ATP energy for the physiological and biochemical activities of the body. The mitogenome was used to investigate whether Hyla and Dryophytos genera are subject to positive selection. In addition, as a unique species in China, the distinction between Hyla sanchiangensis (Anura: Hylidae) and two different sites was also compared and analyzed in this paper. Hyla sanchiangensis (Anura: Hylidae) is endemic to China and is distributed across Anhui, Zhejiang, Fujian, Guangdong, Guangxi, Hunan, and Guizhou provinces. The mitogenomes of H. sanchiangensis from two different sites (Jinxiu, Guangxi, and Wencheng, Zhejiang) were sequenced. Phylogenetic analyses were conducted, including 38 mitogenomes of Hylidae from the NCBI database, and assessed the phylogenetic relationship of H. sanchiangensis within the analyzed dataset. Two mitogenomes of H. sanchiangensis showed the typical mitochondrial gene arrangement with 13 protein-coding genes (PCGs), two ribosomal RNA genes (12S rRNA and 16S rRNA), 22 transfer RNA (tRNA) genes, and one non-coding control region (D-loop). The lengths of the 12S rRNA and 16S rRNA genes from both samples (Jinxiu and Wencheng) were 933 bp and 1604 bp, respectively. The genetic distance (p-distance transformed into percent) on the basis of the mitogenomes (excluding the control region) of the two samples was calculated as 4.4%. Hyla sanchiangensis showed a close phylogenetic relationship with the clade of (H. annectans + H. tsinlingensis), which was supported by ML and BI analyses. In the branch-site model, five positive selection sites were found in the clade of Hyla and Dryophytes: Cytb protein (at position 316), ND3 protein (at position 85), and ND5 protein (at position 400) have one site, respectively, and two sites in ND4 protein (at positions 47 and 200). Based on the results, we hypothesized that the positive selection of Hyla and Dryophytes was due to their experience of cold stress in historical events, but more evidence is needed to support this conclusion.